Study On the Design of High-Power Engines Crankshafts - Sergio Baragetti (Current Approaches in Science and Technology Research Vol. 10, 2021)
This chapter reports some useful criteria for the design of high-power engine crankshafts. Theoretical, numerical FEM – Finite Element Modelling and experimental procedures will be considered. The comparison among the three approaches (Theoretical, Numerical and Experimental – TNE) will allow the designer to increase confidence during the production phase of the components, and increase reliability and structural health.